Evaluation of OO Software Quality by Using Predictive Object Points (POP) Metric - Vijay Yadav, Raghuraj Singh, Vibhash Yadav (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Software quality assessment is essential as it reduces costs associated with the allocation of testing and maintenance resources. Software quality metrics based on object-oriented technologies will become increasingly important as object-oriented technologies become more prevalent. This paper examines how Predictive Object Point software sizing metrics can help designers assess an OO system’s quality during the planning phase. By combining high-level quality attributes such as extendibility, reusability, flexibility, understandability, functionality, and effectiveness, POPs Metric makes it easy to make quality decisions. Different versions of three OO software were tested for the exact necessities and aimed to evaluate the proposed quality assessment model. Various design metrics have been measured using a quality metric tool to assess the quality of the projects under study. We compare POP counts with these quality attributes to see what’s trending. Analysis and presentation of the results demonstrate that the POP Count can be used to assess the quality of OO software.